Cannabinoid Receptor 1 Gene Polymorphisms and Nonalcoholic Fatty Liver Disease in Women with Polycystic Ovary Syndrome and in Healthy Controls - Justyna Kuliczkowska Plaksej; Lukasz Laczmanski; Andrzej Milewicz; A. Lenarcik-Kabza; Anna Trzmiel-Bira; Urszula Zaleska-Dorobisz; Felicja Lwow; Lidia Hirnle (International Journal of Endocrinology)
Context. Polycystic ovary syndrome (PCOS) is frequently associated with nonalcoholic fatty liver disease (NAFLD). The endocannabinoid system may play a crucial role in the pathogenesis of NAFLD. Polymorphism of the cannabinoid receptor 1 gene (CNR1) may be responsible for individual susceptibility to obesity and related conditions. Objective. To determine the role of genetic variants of CNR1 in the etiopathology of NAFLD in women with PCOS. Design and Setting. Our department (a tertiary referral center) conducted a cross-sectional, case-controlled study. Subjects. 173 women with PCOS (aged 20–35) and 125 healthy, age- and weight-matched controls were studied. Methods. Hepatic steatosis was assessed by ultrasound evaluation. Single nucleotide polymorphisms of CNR1 (rs806368, rs12720071, rs1049353, rs806381, rs10485170, rs6454674) were genotyped. Results. Frequency of the G allele of rs806381 (P<0.025) and the GG genotype of rs10485170 (P<0.03) was significantly higher in women with PCOS and NAFLD than in PCOS women without NAFLD. Frequency of the TT genotype of rs6454674 was higher in PCOS women with NAFLD (not significantly, P=0.059). In multivariate stepwise regression, allele G of rs806381 was associated with PCOS + NAFLD phenotype. Conclusion. Our preliminary results suggest the potential role of CNR1 polymorphisms in the etiology of NAFLD, especially in PCOS women.